Remark on boundary data for inverse boundary value problems for the Navier–Stokes equations. (15th September 2015) - Imanuvilov, O Yu; Yamamoto, M
Abstract: In this note, we prove that for the Navier–Stokes equations, a pair of Dirichlet and Neumann data and pressure uniquely correspond to a pair of Dirichlet data and surface stress on the boundary. Hence the two inverse boundary value problems in Imanuvilov and Yamamoto (2015 Inverse Probl. 31 035004 ) and Lai et al ( Arch. Rational Mech. Anal. ) are the same.